Education, Power and Personal Biography: An Interview with Carlos Alberto Torres. - Armando Alcántara Santuario (Universidad Autónoma de Baja California, 2000)
This conversation touches on crucial aspects of the work and research technique of one of Latin America's most outstanding authors in the field of the political sociology of education. During this interview Professor Torres points out some of the principal themes of his research agenda, as well as what he considers Latin America's most important contributions to the discussion of educational problems. Prof. Torres also gives a detailed account of the way he became interested in studying Paulo Freire's work, which he has helped to disseminate in the USA. He explains the way in which he deals with theoretical and methodological problems in his research, as well as the advantages and disadvantages of being a Latin American studying international education while living and working in the United States. Finally, he makes some suggestions for those who are beginning their research on the educational problems of Mexico and Latin America.